O mundo do trabalho dos (as) migrantes venezuelanos (as) que vivem na Paraíba - Capistrano, Valnise Lima Véras (2021)
Venezuela has been suffering an economic and political crisis for several years, which intensified with the fall in oil prices in 2015. Since then, there have been shortages of basic commodities, currency devaluation and thousands of Venezuelans have chosen to leave their country in search of survival and employment, as the salary in Venezuela was not enough to cover the basic needs of a family. This research investigates the public policies for the reception of Venezuelan immigrants in Paraíba and their impact on the employment situation of these migrant arrivals through the process of internalisation in the Casa do Migrante, located in the municipality of Conde, PB, about 21.5 km from the capital of Paraíba. The study also aims to understand the phenomenon of international migration, the motivations for choosing Brazil as a destination country and, especially, how the arrival of Venezuelans to the state of Paraíba occurred, since there are no borders with other countries and the state is more than 5,000 km from Roraima, the main route of entry of these people into Brazil. In this way, the advances in the defence of the human rights of migrants and refugees were verified, verifying the gaps and deficiencies in the treatment given to these people in Brazil, considering the binding norms of international law, as well as the applicability of the law to national norms: the Federal Constitution of 1988, the Refugee Statute, the Migration Law and the Consolidation of Labour Laws. In addition, the theme is related to aspects of the world of work of these people, addressing their labour and employment relations and the current labour situation in which migrants live in Paraíba since 2018. The methodology presented is qualitative research with an exploratory study of descriptive approach through interviews with six Venezuelans, three men and three women aged between 26 and 50 years who arrived in Paraíba through the process of internalization with temporary housing in the house of the migrant in Conde-PB, as well as the coordinator of the house who was also interviewed. The present study concluded that the main motivation for entering Brazil is the search for work and the arrival in Paraíba, by internalisation, facilitates due to the state having shelter with temporary housing. The xenophobia was striking for these people when arriving in Brazil due to their different language. Moreover, it was evident that the State fails in the reception, as it does not guarantee public policies to immigrants to facilitate their access to formal work, not providing the proper reception